A Study to Assess the Effectiveness of Planned Teaching Program on Knowledge regarding Pulmonary Tuberculosis among Clients registered at District Tuberculosis Centre, Pulwama, Jammu and Kashmir - Jan, Rohi; Regu, Mehmooda (International Journal of Nursing Research, 2023)
Aim: The study aimed to assess the existing knowledge regarding pulmonary tuberculosis (TB) among clients before the implementation of the planned teaching program. Materials and Methods: One group pre-test post-test pre experimental approach was adopted for the study. The study was conducted on 57 clients registered at District TB Center, Pulwama, who were selected by total enumerative scattered sampling technique. Data were collected by administering a structured knowledge interview schedule. The content validity of the tool and teaching plan was established. The reliability of the tool was established by testing the internal consistency using test–retest method. Results: The results of the present study indicate that among 57 subjects, 30 (52.63%)subjects had moderately adequate level of knowledge regarding pulmonary TB, 22 (38.60%) subjects had an inadequate level of knowledge, and only 5 (8.77%) subjects had adequate knowledge before planned teaching program, whereas in post-test, the majority of the subjects, 56 (98.25%), had an adequate level of knowledge regarding pulmonary TB and only 1 (1.75%) subject had a moderate level of knowledge after planned teaching program. The mean pre-test knowledge score was 28.31 which improved to 43.68 in post-test (P < 0.001). Conclusion: This study concluded that the planned teaching program is effective tool to improve the knowledge of clients regarding pulmonary TB.